Screening antimicrobial activities of actinomycetes raw extracts from marine ecosystems of Nha Trang and Van Phong Bay, Khanh Hoa Province - Le , Thi Hong Minh; Vu, Thi Thu Huyen; Nguyen, Mai Anh; Vu, Thi Quyen; Vu, Van Nam; Nguyen, Thuy Linh; Doan, Thi Mai Huong; Pham, Van Cuong (Vietnam Journal of Marine Science and Technology, 2025)
Marine actinomyces’ enormous genetic and functional diversity of has led scientist to search for potential secondary metabolite. Among the producers of important natural bioactive compounds discovered, actinomycetes are known to be efficient secondary metabolites with a broad spectrum of biological activities, such as antimicrobial, anticancer, and enzymes. The primary purpose of this study was to isolate and screen for antibacterial activity of potential actinomycete from marine ecosystems of Nha Trang and Van Phong Bay, Khanh Hoa Province, located in the middle-south of Vietnam. The marine actinomycete strains were characterized, and the ethyl acetate extracts were screened for antimicrobial activities using the microtiter broth dilution method. Out of which, the best MIC was produced by G112 and C011 strains. The lowest MIC values result in 16 µg/mL. G112 showed a zone of inhibition against four bacteria and Candida albican. C011 exhibited three different bacterial pathogens. The morphology and genetic results indicated that strain G112 belongs to Streptomyces species, and C011 was identified as a member of Pseudonocardia genus.